Depression as a predictor of work resumption following myocardial infarction (MI): a review of recent research evidence - O'Neil, Adrienne; Sanderson, Kristy; Oldenburg, Brian (Health and Quality of Life Outcomes, 2010)
Depression often coexists with myocardial infarction (MI) and has been found to impede recovery through reduced functioning in key areas of life such as work. In an era of improved survival rates and extended working lives, we review whether depression remains a predictor of poorer work outcomes following MI by systematically reviewing literature from the past 15 years.